EFEKTIFITAS PLATFORM QUIZIZZ SEBAGAI MEDIA EVALUASI PEMBELAJARAN AKIDAH AKHLAK DI MAN 1 KUDUS - Ashif Zafi (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2021)
Abstract: This study aims to determine the application of the Quizizz platform as a medium for evaluating learning Akidah Akhlak in MAN 1 Kudus and to determine the effectiveness of implementing the Quizizz platform as a medium for evaluating learning Akidah Akhlak in MAN 1 Kudus. This research uses descriptive quantitative analysis research. Then, this study gave the results, namely in the evaluation of learning Akidah Akhlak in MAN 1 Kudus during online learning using the Quizizz platform media and in that application it had high effectiveness when it was implemented, namely with a percentage value of 56.17%. The implication of this research for learning is that the online evaluation process is more effective when using the Quizizz platform, especially in daily assessments.